2005
DOI: 10.1007/s00228-005-0945-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between low plasma levels of ophthalmic timolol and haemodynamics in glaucoma patients

Abstract: The plasma concentration of ophthalmic timolol correlates with several haemodynamic effects. As HR decreases, SVRI increases and blood pressure is kept unchanged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…Previous reports on ophthalmic timolol suggest its effects on blood pressure and heart rate in spite of low plasma concentration [12][13][14] mainly during night time. It is contraindicated in patients with bronchial asthma, severe chronic obstructive pulmonary disease, and sinus bradycardia.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous reports on ophthalmic timolol suggest its effects on blood pressure and heart rate in spite of low plasma concentration [12][13][14] mainly during night time. It is contraindicated in patients with bronchial asthma, severe chronic obstructive pulmonary disease, and sinus bradycardia.…”
Section: Discussionmentioning
confidence: 94%
“…7,8) Although some clinical trials have reported that topical PGF2α analogs are safe, [9][10][11] they are thought to cause systemic adverse events. Some examples include ophthalmic timolol or brimonidine, which reduce systemic blood pressure by β-receptor blocking [12][13][14] or α-receptor stimulating actions. 15) It would be difficult to demonstrate the relationship using an epidemiologic study, since the systemic drug adverse events caused by eye drops are very rare.…”
mentioning
confidence: 99%
“…The present study indicates that plasma timolol levels after using 0.1% timolol hydrogel remain low even when the metabolism of timolol is inhibited by paroxetine; the C max of timolol varied between 0.056 and 0.322 ng/ml, i.e., below the suggested threshold of 0.7 ng/ml (Nieminen et al, 2005b;Volotinen et al, 2007). These results imply that paroxetine is unlikely to have a clinically significant effect on the benefit-risk ratio of 0.1% timolol hydrogel.…”
Section: Cyp2d6 Inhibition Raises Ophthalmic Timolol Concentrations 2073mentioning
confidence: 56%
“…In a previous study, the maximum heart rate in an exercise test was decreased by at least 20 beats/min in four of 25 patients after ophthalmic application of 0.5% aqueous timolol (Nieminen et al, 2005b). In these four patients, plasma timolol concentration exceeded 0.7 ng/ml.…”
Section: Cyp2d6 Inhibition Raises Ophthalmic Timolol Concentrations 2073mentioning
confidence: 65%
See 1 more Smart Citation